2010
DOI: 10.1007/s11745-010-3495-z
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Hydrogenated Soybean Oil Exerts Strong Anti‐Prostate Cancer Activities

Abstract: Prostate cancer is the second leading cause of male deaths due to cancer in the United States. Hydrogenated vegetable oils have been suspected of inducing adverse health effects, including atherosclerosis and cancer. Here we report that a selectively hydrogenated soybean oil (SHSO) containing a high quantity of conjugated linoleic acids showed remarkably strong anticarcinogenic activity against prostate cancer in the rat model (Copenhagen rats with MAT-LyLu syngeneic rat prostate cancer cells) study in vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Fatty acid compositions of the perilla oils were analyzed by a gas chromatography (GC) (Shimadzu GC‐2010, Shimadzu Co., Kyoto, Japan) equipped with a flame ionization detector after methyl esterification with sodium methoxide in methanol according to the previous report (Jung and others 2011a).…”
Section: Methodsmentioning
confidence: 99%
“…Fatty acid compositions of the perilla oils were analyzed by a gas chromatography (GC) (Shimadzu GC‐2010, Shimadzu Co., Kyoto, Japan) equipped with a flame ionization detector after methyl esterification with sodium methoxide in methanol according to the previous report (Jung and others 2011a).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, Jung et al (2011) showed, that selectively hydrogenated soybean oil, rich in CLA, exerts strong anti prostate cancer activities, in vivo (rats) and in vitro (human prostate carcinoma cell lines).…”
Section: Cla and Cancermentioning
confidence: 99%
“…The degree of inhibitory effects of CLA against PhIP-induced mutagenicity were estimated at 38% [40]. To confirm the apoptotic activity of CLA against prostate cancer, Jung et al reported anticarcinogenic activity of selectively hydrogenated soybean oil (SHSO) that was modulated with high quantity of CLA [41]. The 5% of dietary SHSO showed the best results to inhibit the prostate cancer in the rat model (Copenhagen rat), by an estimation of 80%.…”
Section: Prostate Cancermentioning
confidence: 99%